Sensory processing sensitivity, anxiety, and short-term heart rate variability in older adults living at high southern latitudes: a brief report - Baeza, Diego; Huirimilla-Casanova, Leyla; Estrada, Claudia; Buccella, Salvador; Castillo-Aguilar, Matías; Núñez-Espinosa, Cristian (Frontiers in Psychiatry, 2026)
BackgroundPopulations living at high southern latitudes are under-represented in aging and psychophysiology research, despite distinctive environmental stressors (long winters, marked seasonality, isolation). Objectives: To test associations between SPS, anxiety, and HRV in community-dwelling older adults living at high southern latitudes.MethodsWe enrolled 101 older adults (mean age 71 years; 72% women) from CADI-UMAG. SPS was measured with the 27-item Highly Sensitive Person Scale (HSPS) and anxiety with the Beck Anxiety Inventory (BAI, clinical cut-off ≥16). HRV (5-min artifact-free) was recorded at rest and after a 2-min step/knee-raise test. Bayesian hierarchical models (medians, 95% CrI, pd, ROPE, BF10) accounted for within-subject correlation and seasonality.ResultsHSPS was positively associated with anxiety: a 1-SD increase in HSPS corresponded to a 0.422-SD increase in BAI. Seasonality showed strong evidence for a null effect (BF10 = 0.08). BAI showed no meaningful associations with resting HRV indices—RMSSD (BF10 = 0.046), SDNN (0.200), HF (0.070), LF (0.032), VLF (0.038)—and HSPS did not moderate BAI–HRV links nor HRV responses to exercise (e.g., ΔRMSSD–BAI median 0.003; ROPE = 100%).ConclusionsIn older adults living at high southern latitudes, SPS appears to be associated with anxiety but not to conventional short-term HRV markers, suggesting SPS may reflects psychological vulnerability rather than parasympathetic dysfunction detectable with brief HRV recordings. These findings highlight the need for context-aware mental-health strategies for highly sensitive older adults in understudied southern populations.